PENELITIAN PENDAHULUAN PEMBUATAN SEL AMOBIL STREPTOMYCES SP DENGAN MENGGUNAKAN MATRIKS KOLOID TITANIUM (IV) HIDROKSIDA DALAM AGAR - Gusnidar K, Tutus
Preliminary study of immobilized Streptomyces sp S21 cells isolated and purified from soil bacteria was carried out; the cells were fixed to colloid particles of titanium (IV) hydroxyde in 2% agar gel. For this purpose, solution of titanium (III) chloride was oxydized first by slow addition of 30% hydrogen peroxyde solution, that followed by neutralization and precipitation with 2 N ammonium hydroxyde solution. Bacterial cells suspension fixed to colloid particles was used as matrices in agar gel, sliced in 5 x 5 x 5 mm size and soaked in cold solution of 0,3 M potasium chloride. The result of bacterial growth by cultivating Strep tomyces sp S21 in growth medium (containing of glucose, yeast extract, potasium dihydrogenphosphate, ammonium sulphate, magnesium sulphate, zink sulphate and ferrous sulphate) without colloid binding at aeration efficiency 3,494 x 10-6 mol of oxygen per atm per hour per liter of medium, has consumed 50% of medium glucose as the follow ing data : in solution of 1% glucose was reached at 21 hours just like in 3% glucose solution, but in solution of 50% glucose it was reached at 36 hours of incubation. The data was obtained in fermentation of 20 ml cells inoculum in 0,9% sodium chloride solution (absorbance at wavelength 555 nm was 0,7), taken from 21 hours age of cells cultivated on nutrient agar medium. The inoculum was suspended in 200 ml growth medium solution at 30°C as the optimal temperature of incubation. Matrices of the immobilized cells was activated in growth medium as mentioned above at 25°C, 30°C and 3?°C with variation of medium glucose content at 1%, 3% and 5%. Decrease of medium glucose content was resulted most rapid on incubation at 30°C in the growth medium containing of 1% glucose, i.e. 50% glucose consumption was reached at 4$ hours incubation. The activated immobilized cells (at 30°C, 24 hours) could decrease 50% glucose consumption in time, i.e. 10 hours incubation in growth medium that containing of 1% glucose. In further examination, the immobilized cells matrices had shown its activity in solution of p-aminobenzoic acid or L-tryptophan, which was indicated by spectral absorbance decreases of both compounds at 270 nm. In this case, activity of the immobilized cells in paminobenzoic acid solution was lower than its activity in Ltryptophan solutio.